Uji Toksisitas Ekstrak methanol Beberapa Bagian Jaringan Tumbuhan Bayur (Pterospermum subpeltatum C.B. Rob) - Pince Salempa; Alfian Noor; Nunuk Hariani; Tjodi Harlim (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2009)
Bayur  plant    (Pterospermum  subpeltatum  C.B.  Rob)  has  not  been searched  for  their  secondary  metabolites.  However,  this  genes  was  used  as traditional   medicines  such as Pterospermum  javanicum   as cure for dysentry, toothache and Pterospermum  acerifolium   fer itchy drug. From toxicity test by BLST upon various tissues it was found that methanol extract, compared to other parts, has higher value 220 ppm.Keywords:  Pterospermum  subpeltatum  C.B. Rob, tocicity, traditional  medicine, Artemia salina